THE USE OF CLAIM-EVIDENCE-REASONING (CER) TO IMPROVE STUDENTS’ ARGUMENTATIVE ESSAY WRITING BASED ON THE LOCAL CULTURAL PERSPECTIVE: A CLASSROOM ACTION RESEARCH - Laora, Kristina; Amrina Sari, Riski (Jurnal Ilmiah Spectral, 2025)
Argumentative text is one of the texts that contains arguments or statements about a certain thing or phenomenon. This text serves to convince the reader, express the author's view, and prove the truth. This research is a Classroom Action Research; theaim is to see the writing process of STBA Pontianak Semester IV students in Essay Writing class by using CER (Claim-Evidence-Reasoning) framework. This argumentative text also discusses students' perspectives about their cultural background; the three major sub-tribes in West Kalimantan namely; Dayaknese, Malay and Chinese/Tionghoa. The results are 1) The Dayak Ethnic Group stated that the tradition of "Nyocok" or drinking Tuak as a symbol of kinship or solidarity during the certain traditional events. 2) TheMalay Ethnic Group, especially Sambas stated that the tradition of “Kemponan” has been abandoned and it is only a habitual mechanism and 3) The Chinese Ethnic Group stated that the "Tatung" attraction serves as a communal healing ritual, which strengthens collective identity and the continuity of beliefs in the Chinese community.